Endoscopic extraction of biliary stones and a migrated endoclip for acute pancreatitis - Benatta, Mohammed Amine; Barthet, Marc; Desjeux, Ariane; Grimaud, Jean Charles (HepatoBiliary Surgery and Nutrition, 2015)
Endoclips after laparoscopic cholecystectomy (LC) may migrate into the common bile duct leading to stone formation, obstruction, cholangitis, stenosis and even pancreatitis (1). Fewer than 78 cases of clip migration (CM) have been reported. The time interval for CM varies from 11 d to 20 y (2). Acute pancreatitis (AP) accounts for 8.7% of overall clinical presentation and diagnosis of patients with CM (2). A 74-year-old woman with LC six years earlier was referred for a mild AP diagnosed 2 months ago. Symptoms resolved after medical treatment. The magnetic resonance imaging showed marked dilatation of bile duct with two biliary stones. The latest laboratory tests were within the normal range. At endoscopic retrograde cholangiopancreatography (ERCP) the stones and an unexpected clip were extracted after endoscopic sphincterotomy (EST) (Figure 1A,B). These were lying freely in the cystic duct with almost three clips threatening to migrate (Figure 2). ERCP with EST allows diagnostic and extraction of both clip and stones, without complications. Two months later the patient was in satisfactory condition.